Environmental and Technological Dimensions of Sustainable Rice Farming Practices in Jonggat Subdistrict, Central Lombok Regency - Nurudin; Nurhayati; Ibrahim Ali; Sukuryadi (Mataram University, 2026)
This study aims to analyze the environmental and technological dimensions of sustainable rice farming practices among rice farming communities in Jonggat Subdistrict, Central Lombok Regency. The research focuses on the integration of cultivation technologies, post-harvest processing, environmental sustainability practices, and the strengthening of farmer institutions to support sustainable agriculture. A descriptive qualitative approach was employed through field observations, in-depth interviews with 20 farmers, and secondary data analysis. Strategic analysis was conducted using the SWOT approach. The results indicate that the adoption of technologies such as the System of Rice Intensification (SRI), organic fertilizers, and the jajar legowo planting system can increase rice productivity by approximately 5–10%. Furthermore, these environmentally friendly agricultural practices contribute to improved soil quality, reduced dependence on chemical fertilizers, enhanced water-use efficiency, and lower greenhouse gas emissions, thereby supporting sustainable environmental management. Nevertheless, technology adoption remains constrained by limited capital, low technological literacy, and continued dependence on subsidized chemical fertilizers. Therefore, strategic efforts such as agricultural digitization, strengthening farmer institutions, continuous extension services, and the development of healthy food certification systems are recommended to improve environmental sustainability and increase the economic value of agricultural products.